2000
DOI: 10.1038/35000041
|View full text |Cite
|
Sign up to set email alerts
|

DNA-replication/DNA-damage-dependent centrosome inactivation in Drosophila embryos

Abstract: During early embryogenesis of Drosophila melanogaster, mutations in the DNA-replication checkpoint lead to chromosome-segregation failures. Here we show that these segregation failures are associated with the assembly of an anastral microtubule spindle, a mitosis-specific loss of centrosome function, and dissociation of several components of the gamma-tubulin ring complex from a core centrosomal structure. The DNA-replication inhibitor aphidicolin and DNA-damaging agents trigger identical mitotic defects in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 33 publications
10
139
2
2
Order By: Relevance
“…Centrosomes are becoming key structures of interest, containing an abundance of mitotic control and DNA damage response factors (Takada et al, 2003;Löffer et al, 2006;Jackman et al, 2003;Golsteyn et al, 1995;Tsvetkov et al, 2003). This thesis shows evidence correlating with previous investigations in other systems, in which centrosomes were inactivated as the end-result of DNA damage induced pathways in mitosis (Sibon et al, 2000;Sibon, 2003;Takada et al, 2003;Löffer et al, 2006). Furthermore, it is possible that the control of CEP63 centrosome function by ATM and ATR could potentially participate in preventing genomic instability and cellular transformations, in which centrosomes role has been proven (Basto et al, 2008).…”
Section: Atm and Atr Inhibition Of Xcep63 Regulatory Role In Spindle supporting
confidence: 68%
See 1 more Smart Citation
“…Centrosomes are becoming key structures of interest, containing an abundance of mitotic control and DNA damage response factors (Takada et al, 2003;Löffer et al, 2006;Jackman et al, 2003;Golsteyn et al, 1995;Tsvetkov et al, 2003). This thesis shows evidence correlating with previous investigations in other systems, in which centrosomes were inactivated as the end-result of DNA damage induced pathways in mitosis (Sibon et al, 2000;Sibon, 2003;Takada et al, 2003;Löffer et al, 2006). Furthermore, it is possible that the control of CEP63 centrosome function by ATM and ATR could potentially participate in preventing genomic instability and cellular transformations, in which centrosomes role has been proven (Basto et al, 2008).…”
Section: Atm and Atr Inhibition Of Xcep63 Regulatory Role In Spindle supporting
confidence: 68%
“…Originally, a report by Sibon et al, showed that unreplicated DNA or incorporation of DNA damage can induce the loss of centrosome function in Drosophila embryos in mitosis. This loss of centrosome function was associated with the displacement of -TuRCs, which led to the formation of insufficient spindle structures that were unable to segregate chromosomes (Sibon et al, 2000). In this situation centrosome inactivation occurs after checkpoint failure in response to DNA damage at the point of mitosis onset.…”
Section: Growing Evidence Of Centrosomal Checkpoints Responding To Dnmentioning
confidence: 99%
“…If centrosomes are experimentally ablated, somatic cells can still form mitotic spindles, but half of the cells fail to complete a normal cytokinesis and arrest in the G 1 -phase [37,44,45]. In Drosophila, defects in DNA are relayed to the centrosome leading to centrosomal and spindle abnormalities, which are hypothesized to be part of a checkpoint for culling of damaged nuclei [46]. Furthermore, centrosomal abnormalities in cancer cells have been frequently observed [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…En résumé, cette étude récente a permis d'établir un lien inattendu entre le méta-ainsi expliquer, par exemple, l'origine de la perturbation de l'expression de protéines centrosomales en présence de dommages à l'ADN [7,8]. Afin de comprendre plus en détail le mécanisme moléculaire modulant la rétention nucléaire des ARNm induite par Chk2, nous avons focalisé notre attention sur un groupe bien particulier de transcrits, qui codent pour les protéines d'histones.…”
Section: Resultsunclassified
“…L'épithélium embryonnaire ainsi formé contiendra environ 6 000 cellules progé-nitrices nécessaires à la formation des tissus somatiques de l'adulte [5]. Or, il a précédemment été démontré qu'en réponse à différents stress génotoxiques subis durant les cycles mitotiques 10 à 13, un processus de triage sera enclenché afin d'induire la chute des noyaux endommagés vers le cytoplasme central de l'embryon, où ils seront détruits [6, dGrip85, suggérant ainsi que la perturbation de l'activité normale de cet organite pourrait faciliter l'élimination des noyaux associés [8]. De plus, les auteurs ont souligné l'implication dans ce processus de la kinase Chk2, encodée par le gène mnk (maternal nuclear kinase) chez la drosophile.…”
unclassified